THE TAX COMPLIANCE PARADOX - Wijaya, Kurnia Mahanani; Rochmatullah, Mahameru Rosy (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study examines the influence of thin capitalization, intellectual capital, capital intensity, and institutional ownership on tax avoidance in manufacturing firms listed on the Indonesia Stock Exchange (IDX) during 2020–2022. Samples were selected based on consistent inclusion in the IDX and availability of complete audited reports in Indonesian rupiah. Data were obtained from www.idx.co.id and company websites and analyzed using multiple linear regression in SPSS 25. Thin capitalization denotes a debt-heavy capital structure, intellectual capital reflects intangible resource utilization, capital intensity measures fixed asset investment, and institutional ownership indicates institutional shareholding proportion. Results show that thin capitalization, intellectual capital, and institutional ownership have no significant effect on tax avoidance, while capital intensity has a significant positive effect. This suggests that greater investment in fixed assets may facilitate legal tax minimization, whereas the other factors exert minimal direct influence. Keywords: Capital Intensity; Institutional Ownership; Intellectual Capita; Tax Avoidance;Thin Capitalization